PHYSICO AND BIOCHEMICAL ANALYSIS OF SUBSURFACE WATERS NEAR POLLUTED SURFACE WATER SOURCE FOR QUALITY EVALUATION - K. JHANSI LAKSHMI; P.V.S. MACHIRAJU; P. UDAYA BHASKAR (International Journal of Pharma and Bio Sciences, 2013)
The focus of the present research study is to characterize the subsurface waters from 12 rural and urban locations of Peddapuram and Kakinada of East Godavari Districts. The sub surface sample drawn during pre monsoon and post monsoon seasons in the habitations of the nearby polluted surface water sources in the revenue divisions are for the purpose of physicochemical and biochemical parameters towards assessing their suitability for drinking and domestic utility. The physicochemical parameters studied include pH, EC, TDS, TH, TA, Ca, Mg, Na, K, Cl-, SO4-2 and PO4-3. In terms of IS: 10500-1992 standards, the results of the studied parameters do not recommend the suitability of these waters either for drinking purpose or for other domestic purposes. Further bacterial species (spp) viz., E.Coli, Pseudomonas, Enterobactor, Klebsiella and Proteus were also observed in these ground water samples confirming their unsuitability for drinking purposes and have concern for human health.